Level and profile of internalizing behaviors problem among preschool children: evidence from Malaysia - Ahmad, Nor Fairani; Mansor, Mariani; Madon, Zainal; Abu Samah, Asnarulkhadi; Zeehan, Farah (Canadian Center of Science and Education, 2016)
Internalizing problems such as depression and anxiety disorders were prevalent in early childhood and these problems could lead to increasingly poor outcomes during school age then later in adult life. The main objectives of this paper were to examine the distribution and identify the level of internalizing behaviours problem among preschool children in Malaysia. Also, to come out with a profile of the children who were in the borderline and clinical status of internalizing problems. A total of 551 (46%) out of 1198 children age four and below were conveniently selected for this study that consist of those who were in the borderline and clinical range of having internalizing problems as rated by parents using the Child Behavioural Checklist for Age 1 ½-5 (CBCL/1 ½ –5). Descriptive statistics such as mean, standard deviation, t-test, ANOVA and correlation tests were applied in data analysis. Results revealed that level of internalizing problems among preschool children in Malaysia was high whereby 338 in clinical and 213 in borderline which represent about 28% and 18% of the total study samples respectively. Overall, female children with the age 3 years old, first born with 2 siblings and live with both parents were the most having internalizing problems. Most of these children had parents in the 30s age range and majority had secondary higher education background. Findings from this study provide evidences that early detection and intervention is crucially needed to prevent continuity of internalizing problems into school age and later to adulthood.